Fetal Echocardiographic Characteristics of Fused Heart in Thoracopagus Conjoined Twins. Issue 7 (10th May 2014) - Wu, Yu; Lv, Qing; Xie, Ming‐Xing; Wan, Lin‐Yuan; Ren, Ping‐Ping; Ge, Andrew; Ge, Shuping
Mini‐Abstract Conjoined twins (CT) are rare with possible serious malformations in which soft tissue, bone, or some organs are joined in utero. The extent of cardiac fusion and intracardiac anatomy of CT determine the viability, natural history, and outcome of potential surgical intervention. Early prenatal diagnosis and assessment may provide a window of opportunity to counsel the family for their informed decision on the pregnancy and to plan for prenatal and perinatal care. In this report, we describe a case of thoracopagus twins diagnosed by fetal echocardiography at 23‐week gestation. The 2 hearts fused at the atrial and ventricular levels. The outcome and review of literature on fetal echocardiographic characteristics of this malformation are discussed.